Informal Space Utilization Shifting post-Urban Revitalizationin the Semarang Old City - Santy Paulla Dewi; Retno Susanti; Grandy Lorenessa Wungo (Faculty of Geography, Universitas Gadjah Mada, 2023)
The Semarang Old City revitalization has changed its physical appearance significantly, from a slum and crowded area to a more organized, pleasant, and attractive one. The revitalization is one of the Mayor's missions after being reelected in 2015 to enhance the Old City’s image as a prominent historical tourist destination. The government established a regulation prohibiting informal activities in the Old City. Informality is considered an interference in urban areas, including spaces that accommodate informal activities through illegal acquisition. However, informal activities persist in the Old City, shifting the physical setting and transforming the spatial utilization. Therefore, this study aimed to examine the transformation of informal spaces in the Old City after revitalization. Quantitative methods were used by distributing questionnaires to informal activity workers and interviews with the Old City manager. The results showed spatial utilization and relation transformations, a close relationship between informal and formal activities, and no conflict regarding spatial utilization. However, the relationship between formal and informal spaces changed after the revitalization. Formal activities prefer clear spatial boundaries, making informal space utilization and pattern more dynamic.